2000
DOI: 10.1002/(sici)1099-0844(200006)18:2<143::aid-cbf857>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iodide on total antioxidant status of human serum

Abstract: Free radicals and subsequent lipid peroxidation have been implicated in the pathogenesis of several degenerative and chronic diseases which are also treated frequently in spas. There are some data arising from previous studies which support an antioxidant or scavenging effect of iodide, being the essential ingredient of a therapeutically used local brine. The aim of the study was to test the antioxidant capacity of iodide in human serum. For this reason we measured the so-called Total Antioxidant Status determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 7 publications
1
18
0
3
Order By: Relevance
“…This is in line with the observation that I 2 treatment of patients with benign breast disease led to a bilateral reduction in breast size and a remission of disease symptoms, which was not observed when iodide was administered (17). Other authors have proposed that iodine, if ingested as I 2 at concentrations higher than 3 mg per day, acts as an antioxidant and prevents lipoperoxidation in various organs, including the brain (18). In a recent study, Delgado et al (19) supplemented Sprague-Dawley rats with I 2 and KJ in drinking water.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the observation that I 2 treatment of patients with benign breast disease led to a bilateral reduction in breast size and a remission of disease symptoms, which was not observed when iodide was administered (17). Other authors have proposed that iodine, if ingested as I 2 at concentrations higher than 3 mg per day, acts as an antioxidant and prevents lipoperoxidation in various organs, including the brain (18). In a recent study, Delgado et al (19) supplemented Sprague-Dawley rats with I 2 and KJ in drinking water.…”
Section: Discussionmentioning
confidence: 99%
“…In fruheren Studien wurde gezeigt, dass der antioxidative Status durch die Zufuhr von Iodid im Rahmen einer Bad Haller Kur positiv beeinflusst werden kann [7,15], da Iodid als Antioxidans and Sauerstoffradikalfdnger wirkt [11] and das antioxidative Potential im Serum and der Tranenflussigkeit erhohen kann [12].…”
Section: Hintergrundunclassified
“…Animal studies (10,22,23) and in vitro studies (23 -25) demonstrated the anticarcinogenic effects of seaweeds against mammary carcinogenesis. Iodine as well as other components of seaweeds have been suggested to act as antioxidants (26) and induce apoptosis in human breast cancer cell lines (23) . In an ecological study, the regions where iodine intake was low had higher breast cancer mortality rates (27) .…”
mentioning
confidence: 99%